Comparative Transcriptome Profiling Reveals a Potential Role of Type VI Secretion System and Fimbriae in Virulence of Non-O157 Shiga Toxin-Producing Escherichia coli - Aas, Christina G.; Drabløs, Finn; Haugum, Kjersti; Afset, Jan E. (Frontiers in Microbiology, 2018)
Shiga toxin-producing Escherichia coli (STEC) cause both sporadic infections and outbreaks of enteric disease in humans, with symptoms ranging from asymptomatic carriage to severe disease like haemolytic uremic syndrome (HUS). Bacterial virulence factors like subtypes of the Shiga toxin (Stx) and the locus of enterocyte effacement (LEE) pathogenicity island, as well as host factors like young age, are strongly associated with development of HUS. However, these factors alone do not accurately differentiate between strains that cause HUS and those that do not cause severe disease, which is important in the context of diagnosis, treatment, as well as infection control. We have used RNA sequencing to compare transcriptomes of 30 stx2a and eae positive STEC strains of non-O157 serogroups isolated from children < 5 years of age. The strains were from children with HUS (HUS group, n=15), and children with asymptomatic or mild disease (non-HUS group, n=15), either induced with mitomycin C or non-induced, to reveal potential differences in gene expression levels between groups. When the HUS and non-HUS group were compared for differential expression of protein-encoding gene families, 399 of 6119 gene families were differentially expressed (log2 fold change ≥ 1, FDR < 0.05) in the non-induced condition, whereas only one gene family was differentially expressed in the induced condition. Gene ontology and cluster analysis showed that several fimbrial operons, as well as a putative type VI secretion system (T6SS) were more highly expressed in the HUS group than in the non-HUS group, indicating a role of these in the virulence of STEC strains causing severe disease.